Escola em tempos de pandemia: atendimento de crianças com transtorno do espectro autista - Santos, Tatiane Cristina Gomes Franco dos (Universidade Federal de São Carlos, 2024)
This course completion work seeks a reflective approach to education in times of the Covid-19 pandemic and its consequences in the learning process of students with au-tism spectrum disorder (ASD). Bringing a rensino remoto emergencialing about the impact of the pandemic on school education and the implementation of remote educa-tion systems through platforms for online classes. The text also contains a brief presen-tation about autism in its clinical, legal and educational aspects. As well as a personal report from the mother of an autistic student who experienced school education during the pandemic period and the operation of remote classes. Finally, this work considers the importance of school for students with ASD in its face-to-face model, strengthening relationships of inclusion, socialization, association and insertion of autistic people in the space they experience on a daily basis.
School during a pandemic: serving children with autism spectrum disorder
Keywords: Educação; Transtorno do Espectro Autista (TEA); Covid-19; Education; Autism Spectrum Disorder (ASD); CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO